Analisis penyebab PHK di PT. Indofood dan hak hak pekerja yang di PHK menurut UU ketenagakerjaan (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Termination of employment (PHK) is one of the crucial issues in industrial relations that has a direct impact on the economic and psychological stability of workers. This research aims to analyze the causes of layoffs that occur at PT Indofood Sukses Makmur Tbk and evaluate the fulfillment of workers' rights in accordance with the provisions of labor legislation in Indonesia. The method used is a qualitative approach with literature studies from legal sources, scientific journals, and company documents. The results showed that layoffs at PT Indofood were triggered by various factors, including cost efficiency, organizational restructuring, digital transformation, and the long-term impact of the Covid-19 pandemic. In addition, there are indications that the implementation of layoffs has not fully complied with legal provisions, such as the lack of a bipartite process and inappropriate compensation. This study concludes that although layoffs are the right of companies, their implementation must still pay attention to the principles of justice, transparency, and protection of workers' normative rights. It is necessary to increase government supervision and strengthen the role of labor unions in order to create harmonious and sustainable industrial relations.Keywords: Termination of Employment, PT Indofood, workers' rights, Labor Law, labor unions, unilateral layoffs